Experimental investigation of a novel wave energy floating platform for hybrid wind-wave applications: The OctaPlat (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The work presents the process of model design and testing and the experimental results for the OctaPlat, a new wave energy floating platform, conceived at IST/ULisboa. A physical model was designed on the basis of the Octaplat concept, which comprises five oscillating water columns (OWCs). The physical model design considered only three of the five OWCs due to infrastructure constraints and was made of acrylic material on a scale of 1:100th scale. The experimental campaign comprised free decay tests and tests under both regular and irregular wave conditions. Different power take-off systems for OWCs (impulse air turbines) were approximated through small orifices. Parameters such as RAO, dimensionless pressure, and the capture width ratio (CWR) were determined and analysed to understand the model performance under different conditions. Under regular waves, the results showed that the coupled hydrodynamic interaction between pitch and surge motions mainly affects the chambers located at the outer edges of the platform. Furthermore, the RAOs of the OWCs seem to be influenced by the natural coupled heave frequency, the natural frequencies of OWC1 and OWC3, and possibly the submultiple of the coupled heave natural frequency (k=1.5). Results also show that the different orifice plates considerably affect the CWR and the peaks' frequencies of its maximum values. Under irregular waves considering full-scale values, for a 2.5 m significant wave height, the peak pneumatic power reached 1.6 MW at 0.077 Hz with an equivalent rotor air turbine diameter of 6.3 m (that is, 30 mm orifice diameter) and 1.9 MW at 0.083 Hz with an equivalent rotor air turbine diameter of approximately 4 m (i.e., 20 mm orifice diameter). For a significant wave height of 3.4 m, the 30 mm orifice produced 3.6 MW at 0.077 Hz, while the 20 mm orifice reached 3.8 MW at 0.091 Hz. These results confirm the platform's feasibility for megawatt-scale wave energy conversion, supporting a key claim of this technology. The experimental results were compared with the numerical ones in terms of CWR. Good agreement was found between both, with a coefficient of determination (R^2) of about 0.94, and the relative difference between them was always less than 20%, except for a few peak deviations.